A Systematic Review and Meta-Analysis on Post-Abortion Contraceptive Utilization and Associated Factors in Ethiopia - Getu Engida Wake; Girma Wogie Fitie; Michael Amera Tizazu (Frontiers Media S.A., 2022)
BackgroundPost-abortion contraceptive utilization is the initiation and use of family planning methods at the time of management of abortion or before fertility returns. A significant discrepancy was reported regarding the prevalence and its associated factors of post-abortion contraceptive utilization in Ethiopia. So, this systematic review and meta-analysis aimed to estimate the pooled prevalence of post-abortion contraceptive utilization and its associated factors in Ethiopia.MethodsPreferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guideline was used. The databases such as PubMed, Google Scholar, Science Direct, Cochrane library, Scopus, CINAHL, Web of Science, and additional searches by using direct Google search, libraries, and preprint were searched. Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) was used for critical appraisal.ResultsA total of 17 studies with 13,075 individuals were included. Of these, 14 studies with 5,719 individuals were used to estimate the prevalence. The pooled prevalence of post-abortion contraceptive utilization in Ethiopia was 63.64% (95% CI: 57.75-69.53). The subgroup analysis reported the highest prevalence of post-abortion contraceptive utilization in a study conducted in Addis Ababa (77.40%), a study published in 2015-2021 (66.15%), and among studies with a sample size >400 (66.84%). The pooled odds ratio (OR) of post-abortion contraceptive utilization for the mothers who had post-abortion family planning counseling was 4.15 (95% CI = 1.30, 13.2), and history of family planning utilization was 4.28 (95% CI = 2.66, 6.89).ConclusionsThe pooled prevalence of utilization of post-abortion contraceptives in this meta-analysis remains low. Post-abortion family planning counseling and the history of the utilization of modern family planning methods were significantly associated with the practice of post-abortion contraceptives. The Ministry of Health should encourage post-abortion family planning utilization, making more efforts on post-abortion contraceptive counseling. Health facilities should work hard to strengthen the family planning counseling service, especially focusing on those who had no previous family planning utilization.